Synthesis of threo- and erythro-configured trihydroxy open chain lipophilic ketones as possible anti-mycobacterial agents. Issue 1 (15th January 2017) - Borkar, Santosh Ramdas; Bokolia, Naveen; Aidhen, Indrapal Singh; Khan, Inshad Ali
Graphical abstract: Abstract: A series of threo - and erythro -configured open-chain trihydroxy ketones was synthesized starting froml - andd -ascorbic acid respectively as the starting material, through the use of Grignard reactions for the requisite CC bond formations. The lipophilic ketones were screened against Mycobacteriumtuberculosis for anti-proliferative activity. The lipophilic ketones with tetradecyl alkyl side chains were found to be moderately active against cell proliferation. Abstract : 1-Ethyl-2- O -benzyl-(3, 4- O -isopropylidene)-l -threose: C16 H22 O4 [ α ]D 23  = +37.0 ( c 1.0, CHCl3 ) Source of chirality: Chiral pool synthesis Abstract : 1-Ethyl-2- O -benzyl-(3, 4- O -isopropylidene)-d -erythrose: C16 H22 O4 [ α ]D 23  = +43.4 ( c 1.0, CHCl3 ) Source of chirality: Chiral pool synthesis Abstract : 1-Ethyl-(3, 4- O -isopropylidene)-l -threose: C9 H16 O4 [ α ]D 23  = −33.8 ( c 1.0, CHCl3 ) Source of chirality: Chiral pool synthesis Abstract : 1-(Ethyl)-(3, 4- O -isopropylidene)-d -erythrose: C9 H16 O4 [ α ]D 23  = −96.5 ( c 1.0, CHCl3 ) Source of chirality: Chiral pool synthesis Abstract : 1-Ethyl-l -threose or (4 R, 5 S )-4, 5, 6-trihydroxyhexan-3-one: C6 H12 O4 [ α ]D 23  = −33.0 ( c 05, MeOH) Source of chirality: Chiral pool synthesis Abstract : 1-(Ethyl)-d -erythrose or (4 R, 5 R )-4, 5, 6-trihydroxyhexan-3-one: C6 H12 O4 [ α ]D 23  = −14.5 ( c 1.0, CHCl3 ) Source of chirality: Chiral pool synthesis Abstract : 1-Morpholino-(3, 4- O -isopropylidene)-l -threonamide: C11 H19 NO5 [ α ]D 23  = −10.95 ( c 1.0, CHCl3 ) Source of chirality: Chiral pool synthesis Abstract : 1-Morpholino-(3, 4- O -isopropylidene)-d -erythronamide: C11 H19 NO5 [ α ]D 25  = −23.35 ( c 1.0, CHCl3 ) Source of chirality: Chiral pool synthesis Abstract : 1-Morpholino-2- O -benzyl-(3, 4- O -isopropylidene)-l -threonamide: C18 H25 NO5 [ α ]D 23  = +11.4 ( c 1.0, CHCl3 ) Source of Chirality: Chiral pool synthesis Abstract : 1-Morpholino-2- O -benzyl-(3, 4- O -isopropylidene)-d -erythronamide: C18 H25 NO5 [ α ]D 25  = +38.3 ( c 1.0, CHCl3 ) Source of chirality: Chiral pool synthesis